2013
DOI: 10.1111/jan.12130
|View full text |Cite
|
Sign up to set email alerts
|

A concept analysis of situational awareness in nursing

Abstract: Failures in perception, comprehension, and/or projection can significantly reduce the accuracy and appropriateness of patient care decisions. Therefore, as a precursor to decision making, poor or inadequate levels of situational awareness present serious threats to patient safety. Situational awareness needs to be examined in a theoretical context, studied systematically and openly recognized as a key factor in the delivery of safe patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 38 publications
1
57
0
2
Order By: Relevance
“…). High levels of situational awareness have been linked with a reduction in human error and adverse events, and better patient outcomes (Fore & Sculli ).…”
Section: Discussionmentioning
confidence: 99%
“…). High levels of situational awareness have been linked with a reduction in human error and adverse events, and better patient outcomes (Fore & Sculli ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the use by all of word stems "control" and "overview" implied that they would not leave those functions solely up to the team leader (GP). Utilising the tools for providing an overview, or for sharing information while working in a team, may enhance a shared "situational awareness" (Fore & Sculli, 2013), acquired through processes of situational assessment, one of the core dimensions of teamwork (Wright et al, 2009). Explorations in delivery room settings (Mackintosh, 2009) revealed that providing an overview on a visible whiteboard was one of three key elements facilitating such awareness The other two elements were coordinator and inter-professional "handovers".…”
Section: Discussionmentioning
confidence: 99%
“…A more specific definition refers to it as the awareness of the components within a spatio-temporal environment. This type of awareness helps users instantly understand the elements of the near future that may influence them (Fore and Sculli 2013). Situational awareness helps provide an experience for a product or service without having to continually be aware.…”
Section: Agent-awarenessmentioning
confidence: 99%
“…It is because the effects of the predictability and task-technology fit the agent-awareness of the product or service provides to users (Huang et al 2012;Merikle et al 2001;Fore and Sculli 2013). As it becomes easier to predict the pattern of a product or service, users seek to give their autonomy to an agent-aware product or service.…”
Section: Agent-awarenessmentioning
confidence: 99%